Ebenezer Smith account book - Smith, Ebenezer, 1746-1816.
Account book (174 pages) containing clothing accounts (1780-1783) of Smith's company of the 13th Massachusetts Regiment together with list (1781) of the company members and copies of various orders, resolves, and petitions. Later used by Smith as a justice of the peace docket book (1787-1796) in New Marlborough, Berkshire County, Mass., the volume contains a list of marriages performed.
Microfilm edition available
Microfilm of original in the Manuscript Division.
Continental Army officer amd justice of the peace, of Berkshire County, Mass.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: United States. -- Continental Army -- Registers; United States. -- Continental Army -- Supplies and stores; United States. -- Continental Army. -- Massachusetts Regiment, 13th.; Justices of the peace -- Massachusetts; Marriage records -- Massachusetts -- Berkshire County; Marriage records -- Massachusetts -- New Marlborough; Massachusetts -- History -- Revolution, 1775-1783.; United States -- History -- Revolution, 1775-1783 -- Equipment and supplies; United States -- History -- Revolution, 1775-1783 -- Registers; Army officers; Justices of the peace -- Massachusetts